Spiritual leadership and lecturer performance: mediating role of work motivation - Subhaktiyasa, Putu Gede; Gede Agung, Anak Agung; Jampel, I Nyoman; Dantes, Kadek Rihendra (International Journal of Evaluation and Research in Education (IJERE), 2024)
Spiritual leadership developed from intrinsic motivation is based on ethical and moral values that align with the education system. However, the research is limited in the context of higher education institutions. Therefore, this study aims to provide an understanding of the effect of spiritual leadership on lecturer performance through work motivation. The research design was quantitative, with 120 samples of permanent lecturers in private higher education institutions who have obtained lecturer certificates. Data was collected through a structured questionnaire and analyzed using Smart-PLS. The results showed that spiritual leadership affects lecturer performance and work motivation. In addition, work motivation plays a mediating role with a high effect size. Hence, these findings can serve as a basis for higher education institutions to develop more inclusive and inspiring leadership strategies that integrate spiritual values and create a more motivating work environment for lecturers.